2020
DOI: 10.1021/acsnano.0c01312
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Ti3C2Tx: MXenes for Electromagnetic Interference Shielding

Abstract: New ultrathin and multifunctional electromagnetic interference (EMI) shielding materials are required for protecting electronics against electromagnetic pollution in the fifth-generation networks and Internet of Things era. Micrometer-thin Ti 3 C 2 T x MXene films have shown the best EMI shielding performance among synthetic materials so far. Yet, the effects of elemental composition, layer structure, and transition metal arrangement on EMI shielding properties of MXenes have not been explored, despite the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
407
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 588 publications
(433 citation statements)
references
References 39 publications
4
407
0
Order By: Relevance
“…Han et al reported that the spray coated Ti 3 C 2 T x -MXene layer with 40 nm exhibits 21 dB of EMI SE and most of the MXene with thickness below 10 micron and above skin depth shows EMI SE above 20 dB. Further he added that the Ti 3 C 2 T x MXene displayed good EMI shielding efficiency among other MXenes [ 28 ]. Chen et al explained that the introduction of the silver nanowire considerably improves EMI SE and added that the neat silver nanowire gives rise 21 dB while MXene-welded silver nanowire film exhibits 34 dB with excellent mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al reported that the spray coated Ti 3 C 2 T x -MXene layer with 40 nm exhibits 21 dB of EMI SE and most of the MXene with thickness below 10 micron and above skin depth shows EMI SE above 20 dB. Further he added that the Ti 3 C 2 T x MXene displayed good EMI shielding efficiency among other MXenes [ 28 ]. Chen et al explained that the introduction of the silver nanowire considerably improves EMI SE and added that the neat silver nanowire gives rise 21 dB while MXene-welded silver nanowire film exhibits 34 dB with excellent mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the limited applications of Nb-containing MXenes suggest they might face similar challenges as other hybrid MXene systems. Nb-containing MXenes do show improvement in EMI shielding applications compared to their pure counterparts [62]. For example, Nb y V 2−y CT x (15-36 dB depending on the content of V) performs better than Nb 2 CT x (10-15 dB) in the frequency of 8.2-12.4 GHz in EMI shielding.…”
Section: Applicationmentioning
confidence: 99%
“…For the Mo-containing MXenes, most of the papers focus on synthetic methods with limited applications [60][61][62]. Certainly, hybrid transition metals of Mo-containing MXenes are expected to enable new functions than single transition metal MXenes [60].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 30 stoichiometric MXene structures have been synthesized from the more than 100 predicted compositions, and there have also been reports on the creation of solid solution MXenes. [2][3] MXenes have been utilized in various fields, including energy storage and conversion, electromagnetic interference shielding, nanocomposites, sensors, and biomedical applications. [4][5] As the scope of MXene research has expanded, so too have studies on improving the quality of MXenes by exploring new synthesis routes and processing methods in order to enhance their performance.…”
Section: Introductionmentioning
confidence: 99%